Basic Concepts of Islamic Education According to Abuddin Nata - Idris, M. Arif; Yanti, Cut Mirza (Seutia Hukamaa Cendekia, 2023)
Abuddin Nata is a thinker in Islamic education in Indonesia who is very active in the world of education, especially Islamic education. Therefore, the author is interested in looking further into the basic concepts of Islamic education, according to Abuddin Nata. The aim to be achieved in discussing this thesis is to find out Abudin Nata's views on Islamic education and to find out the implementation of the basic concepts of Islamic education according to Abuddin Nata. The type of research in this scientific work is library research, and the method used in discussing this thesis is content analysis. Abuddin Nata said that the curriculum in Islamic education has principles, namely the principle of perfect connection with religion, including teachings and values. Every part of the curriculum, such as objectives, content, methods, and assessment, must be based on religion. The overall principle of the aims and scope of the curriculum includes fostering faith, reason, physicality, and things that benefit society in spiritual, social, economic, and political development. The principle of the relative balance between objectives and curriculum content; The principle of the relationship between talents, interests, abilities, and needs of students; The principle of maintaining individual differences between students in terms of interests or talents; The principle of accepting developments and changes by the times and places and the principle of the relationship between various subjects and the experiences and activities contained in the curriculum